Perubahan Fungsi Teba di Pekarangan Desa Nyuh Kuning - Utari, Cokorda Istri Arina Cipta (Jurnal Arsitektur Lansekap; Vol.7, No.2, Oktober 2021DO - 10.24843/JAL.2021.v07.i02.p12, 2021)
Teba land change of function at Nyuh Kuning Village. Nyuh Kuning Village is one of four pakraman (traditional) village in Mas Village, Ubud District, Gianyar Regency, Bali Province which has developed well because of its tourism sector. The rapid development of tourism has resulted significant changes in the use of land in this village. This study aims to explore the pattern of teba landuses changes due to tourism, the factors that cause these changes, and the consequences of these changes on green open space. The research method used was qualitative research. The sample selection used was purposive random sampling technique which was processed by systematic triangulation. The result showed that the change of teba was as follows: 22,7% for domestic dwelling, 6,8% for comercial buildings/domestic buildings with half of the land functioned for plantation for religious purposes and for food needs, 15,9% without teba land, 9,1% are still intact, and the rest of 45,5% as a commercial building for financial needs of the community. The factors that affect the change in the function of teba were internal factors; social, economic and cultural. As well as external factors such as political and policy factors. Futhermore, the consequences of changes in the function of the teba have a significant impact on the disruption of the bio-ecological (physical) functions, social and cultural functions, the balance of the ecosystem, and the aesthetic/architectural functions of the traditional Balinese heritage.